2009
DOI: 10.1109/tasc.2009.2018186
|View full text |Cite
|
Sign up to set email alerts
|

Flux Pinning Characteristics of Artificial Pinning Centers With Different Dimension

Abstract: The crystal defects of the nano-scale, which are called artificial pinning centers (APCs), were successfully introduced into high-temperature superconductors (HTS) by nanotechnology, in order to strongly pin the quantized vortices. Critical current densities of the HTS films were dramatically improved by APCs whose dimensions were controlled. By this method, the in-field (77 K) of the high-quality, epitaxial films was improved by one order of magnitude or more compared with the values of the past. A current ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In the case of two-dimensional APCs, the pinning forces were the strongest among APCs of all dimensional, as found by the simulation of the quantum magnetic flux movement inside superconducting films with various APCs, using a time-dependent Landau equation [13]. On the contrary, because a grain boundary that represents the two-dimensional APCs generally works to block a current across a grain boundary, the two-dimensional APCs, such as planelike defects are very difficult to fabricate as effective pinning centers in superconducting films.…”
Section: Introductionmentioning
confidence: 72%
“…In the case of two-dimensional APCs, the pinning forces were the strongest among APCs of all dimensional, as found by the simulation of the quantum magnetic flux movement inside superconducting films with various APCs, using a time-dependent Landau equation [13]. On the contrary, because a grain boundary that represents the two-dimensional APCs generally works to block a current across a grain boundary, the two-dimensional APCs, such as planelike defects are very difficult to fabricate as effective pinning centers in superconducting films.…”
Section: Introductionmentioning
confidence: 72%
“…Another possibility is to consider the relation between the APCs and the superconducting matrix: (i) increasing the number of the structural defects that are naturally present in a superconducting film, such as dislocations [37], stacking faults [38] or grain boundaries [39], (ii) damaging the matrix by heavy ion irradiation, producing columnar defects [22], (iii) subtracting matter in a chemical or physical route, producing nanopores or nanovoids [40], or (iv) adding second phases to the superconducting matrix. The technique of adding the second phase is a large category of APCs and many papers have been recently published on this topic [3,13]. A consequent classification of the APCs is the composition of the second phases: metals (Au [41], Ag [42], and so on), phases belonging to the YBCO phase diagram (Y 2 O 3 [15], Y-211 [43] and so on), perovskites (BaIrO 3 [44], BaHfO 3 [45], BZO [14], BSO [16]) and so on.…”
Section: Artificial Pinning Center Approachmentioning
confidence: 99%
“…However, the small angle grain boundary can be considered as a dislocation array, and there is a possibility of working as strong pinning centers, as suggested by Pan et al [8] when the misorientation angle is small. Matsumoto et al [13] have reported the use of grain boundaries as effective pinning centers in GdBCO films. By varying the oxygen partial pressure during deposition, the size of the grains continuously changed from 196 to 92 nm, as shown in figure 7(b).…”
Section: Two-dimensional Artificial Pinning Centers: Grain Boundary I...mentioning
confidence: 99%
See 1 more Smart Citation
“…The biasing current density predetermines the strength of F L . The force F p depends on the homogeneity of the superconducting thin film's composition [2], structure [3], and geometry (e.g., thickness and/or width) [4]. Thus, F p can be modified * corresponding author; e-mail: arturas.jukna@vgtu.lt using various methods: an introduction of columnar defects into the superconducting film [3], local variations in film's thickness or in chemical composition [2,4], introduction of periodic magnetic barriers [5], etc.…”
Section: Introductionmentioning
confidence: 99%